Actual Situation of Thromboembolic Prophylaxis in Obesity Surgery: Data of Quality Assurance in Bariatric Surgery in Germany. (9th July 2012) - Stroh, Christine; Luderer, D.; Weiner, R.; Horbach, T.; Ludwig, K.; Benedix, F.; Wolff, Stefanie; Knoll, C.; Lippert, H.; Manger, T.
Abstract : Background . Evidence-based data on optimal approach for prophylaxis of deep venous thrombosis (VTE) and pulmonary embolism (PE) in bariatric operations is discussed. Using antithrombotic prophylaxis weight adjusted the risk of VTE and its complications have to be balanced with the increased bleeding risk. Methods . Since 2005 the current situation for bariatric surgery has been examined by quality assurance study in Germany. As a prospective multicenter observational study, data on the type, regimen, and time course of VTE prophylaxis were documented. The incidences of clinically diagnosed VTE or PE were derived during the in-hospital course and follow up. Results . Overall, 11, 835 bariatric procedures were performed between January 2005 and December 2010. Most performed procedures were 2730 gastric banding (GB); 4901 Roux-en-Y-gastric bypass (RYGBP) procedures, and 3026 sleeve gastrectomies (SG). Study collective includes 72.5% (mean BMI 48.1 kg/m 2 ) female and 27.5% (mean BMI 50.5 kg/m 2 ) male patients. Incidence of VTE was 0.06% and of PE 0.08%. Conclusion . VTE prophylaxis regimen depends on BMI and the type of procedure. Despite the low incidence of VTE and PE there is a lack of evidence. Therefore, prospective randomized studies are necessary to determine the optimal VTE prophylaxis for bariatric surgical patients.